PECULIARITIES OF SPEECH ETIQUETTE OF THE UKRAINIANS IN THE EPISTOLARY TRADITION ON THE EDGE OF THE XIX–XX-th THE CENTURIES - Ilkiv, A. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with national peculiarities of speech etiquette on the edge of the XIX–XX-th centuries on the basis of Ukrainian writers’ correspondence. Verbal forms of politeness and epistolary address as the basic components of the communicative contact and emotional indicators of the letter tonality were analyzed. National peculiarity of epistolary address was defined. The research is carried out on the basis of the letters of Olha Kobylyanska, Lesya Ukrainka, Vasyl Stefanyk, Mykhailo Kotsyubynskyi and Volodymyr Vynnychenko.